Teachers' Perspectives on the Utilization of Artificial Intelligence in the Preparation of Social Studies Learning Assessments - Nurhayati, Alfisyah; Rahman, Muhammad Eka; Fitria, Rachma Dini; Mafar, Fiqru; Islami, Novita Nurul; Adibah, Elisa Dourothun Nafis El; Firdaus, Far'i (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2025)
Technological developments, especially Artificial Intelligence (AI), are increasingly popular and utilized in various fields, including education. Teachers should update their technological knowledge to facilitate the learning process. This study explores teachers' perspectives at Jember Residence on utilizing artificial intelligence to prepare explicit social studies learning assessments. The method used in this study is a descriptive qualitative approach through interviews, focus group discussion and questionnaire instruments distributed to social studies teachers in the Jember Regency. The study results indicate that social studies teachers' used Artificial Intelligence (AI) in preparing social studies learning assessments in varies. Based on AI, most teachers favor using artificial intelligence in learning assessments, although it is limited to only a few types of AI. Teachers admit that Artificial Intelligence can increase efficiency and accuracy in preparing and assessing social studies learning assessments. In addition, Artificial Intelligence is also considered capable of providing faster and more specific feedback to students and assisting in personalizing learning. However, this study also revealed several challenges faced by teachers, including limited technological infrastructure, lack of training and technological skills among teachers.